Expressões de religiosidade na festa de Santa Luzia na cidade de Mossoró (RN) - Lima Filho, José Carlos de (2012)
The study of religiosity and of religion in the feast is crucial to the understanding of myth,ritual and symbols inserted in devotion and promise to the saint, taking as inspiration the focus point of the rituals, especially the ritual procession, or even touring runs through the twenty-first century, even at such desecration. The purpose of this research is to reflect on the shifting ritual, different expressions such as gestures, silence, clothing characterized, objects, banners and sounds that are moving the close relations between the pilgrim (devout and/or curious) and the saint. To make this reflection based we decided to depart from a field research for five days, along with visitors, devotees promisers, trying to gather free and spontaneous information, adding to the bibliography, dealing with myth, ritual and symbols used by the walker in the procession of St. Lucy. The objective is to point the name of the various expressions of religious feast of the Patron Saint; to emphasize the importance of the rites as itinerant religious phenomenon in a secularizing society, reflecting the open air rite from a close relationship between the believer and the divine; to understand syncretism and the notion of sacred, using the methodology of participant observation on the feast of St. Lucy in Mossoró (RN)